Bronchobiliary fistula caused by diaphragmatic invasion of a hepatic tumour. (29th August 2018) - Nathani, Alireza; Alley, Maxwell; Modi, Aakash; Narayan, Sunil; Beegle, Scott H
Abstract : A 71-year-old man presented with a productive cough consisting of yellow fluid. He had previously been treated for pneumonia without resolution in his symptoms. Sputum was tested for bilirubin using a urine dipstick given its similar appearance to bile, which was positive. Hepatobiliary scintigraphy scan revealed uptake of radiotracer in the right lower lobe of the lung. Endoscopic retrogade cholangiopancreatography confirmed diagnosis of a bronchobiliary fistula. The patient had a stent placed in the common bile duct promoting anterograde bile flow with complete resolution of symptoms.